1974
DOI: 10.1111/j.1365-2125.1974.tb01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Antipyretic Analgesics, Alone or in Combination With Alcohol, on Human Psychomotor Skills Related to Driving

Abstract: 1 The effect of acetylsalicylic acid (1 g), indomethacin (50 mg), and phenylbutazone (200 mg) on psychomotor skills was examined double blind on 180 volunteer students. Ninety students received ethyl alcohol (0.5 g/kg) and 90 subjects an equal volume of placebo drink in combination with the drugs. 2 Psychomotor skills were measured with a choice reaction test, two co-ordination tests, and a divided attention test, having correlation with traffic behaviour. The subjects assessed their feelings of performance by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…TA is tolerated quite well by the stomach (26), which may explain the lack of gastric side-effects in our study. In man, PG inhibitors inhibit vasodilatation in the chlorpropamide-alcohol test (8) and reduce or enhance the depressant effects of ethanol on psychomotor skills (27). The prolongation of bleeding time caused by ethanol is potentiated by aspirin (28).…”
Section: Discussionmentioning
confidence: 99%
“…TA is tolerated quite well by the stomach (26), which may explain the lack of gastric side-effects in our study. In man, PG inhibitors inhibit vasodilatation in the chlorpropamide-alcohol test (8) and reduce or enhance the depressant effects of ethanol on psychomotor skills (27). The prolongation of bleeding time caused by ethanol is potentiated by aspirin (28).…”
Section: Discussionmentioning
confidence: 99%
“…Linnoila et al . found that a single dose of 50 mg indomethacin slightly impaired performance in driving‐related attention and coordination tests such as a choice reaction time test, two‐coordination test and a divided attention test. On the other hand, Bruce‐Jones et al .…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, the present study is the first to assess the effect of indomethacin on complex attention demanding tasks relevant to falls. Previous research mainly focused on psychomotor functioning . Linnoila et al .…”
Section: Discussionmentioning
confidence: 99%
“…cyclosporin) [175] or even causing adverse reactions e.g. orthostatic hypotension (with felodipine) [176], increased incidence of hepatitis (with isoniazid) [177] or hepatotoxicity (with methotrexate) [178], bleeding (with aspirin) [179], and impaired motor coordination (with phenothiazines and phenylbutazone) [180].…”
Section: Interactions With Alcoholmentioning
confidence: 99%